Dylematy metodologiczne badań kultury politycznej w Internecie - Mider, Daniel (Przegląd Politologiczny, 2018)
This paper concentrates on the analysis of methodological problems of studies conducted using the Internet, in particular on the issue of whether it is reasonable to apply classical research techniques. These considerations start with the reflection on the ontological parameters of the Internet: its physical, socio-psychological and information properties. Next, the paper analyzes four groups of research techniques: surveys of opinion, studies of behaviors, studies of cultural creations, and studies of the structure of the Internet. The subject of analyses involves the range and content of modifications required in order to apply individual research techniques in the Internet.